IL‐6 is associated with expansion of myeloid‐derived suppressor cells and enhanced immunosuppression in pancreatic adenocarcinoma patients. (15th October 2021) - Sharma, Vinit; Sachdeva, Naresh; Gupta, Vikas; Nada, Ritambhra; Jacob, Justin; Sahni, Daisy; Aggarwal, Anjali
Abstract: Chronic inflammation favours the expansion of myeloid‐derived suppressor cells (MDSCs) by secreting pro‐inflammatory mediators. The role of MDSCs in mediating immunosuppression in pancreatic adenocarcinoma and in defining a premalignant route from chronic pancreatitis remains unclear. We aimed to study the immunosuppressive potential of all subsets of MDSCs and their correlation with inflammatory cytokines in pancreatic adenocarcinoma and chronic pancreatitis. Relative frequencies of MDSCs, immunosuppressive markers arginase‐1 (ARG‐1), programmed death‐ligand 1 (PD‐L1), reactive oxygen species (ROS) and cytokines in circulation and surgically resected local pancreatic tissue of chronic pancreatitis and pancreatic adenocarcinoma patients were analysed by multicolour flow cytometry and cytokine bead array, respectively. Levels of cytokines involved in MDSCs activation were analysed by ELISA, and the immunosuppressive nature of MDSCs was confirmed by T‐cell suppression assay. Frequencies of circulating MDSCs and ARG‐1, PD‐L1, and ROS were significantly higher in pancreatic adenocarcinoma than healthy controls and showed a significant positive correlation with MDSCs burden in cancer tissue. Serum levels of cytokines IL‐6, IL‐8 and IL‐10 were significantly elevated in pancreatic adenocarcinoma. IL‐6 serum levels showed a significant positive correlation with frequencies of circulating MDSCs in pancreatic adenocarcinoma patients, and MDSCs mediated suppression of T‐cell proliferation in vitro was associated with elevated IL‐6 levels in the cell culture medium. Collectively, our results suggest that IL‐6 plays a crucial role in the expansion of MDSCs and activating their immunosuppressive nature in pancreatic adenocarcinoma. The relative frequency of MDSCs in circulation can be used as a potential diagnostic biomarker for pancreatic cancer.